1999
DOI: 10.1001/archotol.125.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Volume-Length Impact of Lateral Jaw Resections on Complication Rates

Abstract: Extirpative losses involving more than 5 cm of bone, or tissue volume greater than 240 cm3, are associated with unacceptably high complication rates when reconstructed with solid screw stainless steel plates and this warrants consideration of alternative techniques for long-term stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 14 publications
2
54
0
1
Order By: Relevance
“…7 Others have argued that placing a reconstruction plate across a lateral defect less than 5 cm will yield only a 5% to 10% long-term complication rate that includes plate fracture, intraoral or extraoral exposure, and loosening of the screws of the plate requiring surgical intervention. [8][9][10] Boyd et al 5 used a concept of "days of life lost" for time devoted to repairing failed reconstructions and came to the conclusion that even with a small complication rate for lateral defects, those patients who are young, fit, and not being palliated should receive an osteocutaneous reconstruction. When bolstered by a reconstruction plate, our data show that using the forearm osteocutaneous flap provides superior long-term results compared with historical controls using a soft tissue flap to cover the plate.…”
Section: Discussionmentioning
confidence: 99%
“…7 Others have argued that placing a reconstruction plate across a lateral defect less than 5 cm will yield only a 5% to 10% long-term complication rate that includes plate fracture, intraoral or extraoral exposure, and loosening of the screws of the plate requiring surgical intervention. [8][9][10] Boyd et al 5 used a concept of "days of life lost" for time devoted to repairing failed reconstructions and came to the conclusion that even with a small complication rate for lateral defects, those patients who are young, fit, and not being palliated should receive an osteocutaneous reconstruction. When bolstered by a reconstruction plate, our data show that using the forearm osteocutaneous flap provides superior long-term results compared with historical controls using a soft tissue flap to cover the plate.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike defects which involve the anterior mandibular arch, lateral defects result in disruption of the muscles of mastication and create an imbalance of the forces required to maintain mandibular form and function. A wide variety of reconstruction techniques have been described to restore continuity of the mandible including: nonvascular bone grafting, 1 mandibular bridging with reconstruction plates [2][3][4] and soft tissue or osteocutaneous free flap reconstruction. In a recent study by King et al, 5 patients who underwent vascularized bony reconstruction demonstrated improved functional results when compared to those who underwent soft tissue reconstruction alone.…”
Section: Introductionmentioning
confidence: 99%
“…Although some retrospective clinical studies recommended the use of a modified plate system (Stoll et al, 1992;Gellrich et al, 2004;Lopez et al, 2004), the rate of plate-related complications is still high (Freitag et al, 1991;Stoll et al, 1992;Lavertu et al, 1994;Boyd et al, 1995;Blackwell et al, 1996;Ueyama et al, 1996;Arden et al, 1999;Blackwell and Lacombe, 1999;Minnen et al, 2002;Wei et al, 2003;Lopez et al, 2004).…”
Section: Introductionmentioning
confidence: 99%